THE IMPACT OF MANDALIKA CIRCUIT DEVELOPMENT ON SOCIO-CULTURAL CHANGES : A SYSTEMATIC LITERATURE REVIEW - Noviana, Mila; Malihah, Elly; Komariah, Siti (Universitas Negeri Medan, 2023)
Socio-cultural changes from the existence of a tourism development affect the order in society. The study of socio-cultural changes can be seen from the changing forms of culture in the surrounding community. Socio-cultural changes that can be seen in terms of changes in mindset, behavior patterns, and of course changes in the form of physical objects. For this reason, this study aims to study the impact of the construction of the Mandalika Circuit on socio-cultural changes. The literature search in this study was based on the Google Scholar database, which produced 21 published articles from 2019-2022 using the keyword Mandalika Circuit Development. The Direct Knowledge database with the keywords social impact tourism in the 2018-2022 range of 10 articles. After going through the process of screening, quality assessment, data extraction, and adjustment to the inclusion criteria, 31 articles were obtained as reference articles that could be used in this study. The results of this study obtained various impacts of the construction of the Mandalika Circuit on socio-cultural changes in the form of changes in people™s mindsets and behavior patterns. The mindset and behavior of the community towards progress and its impact are in the eyes of the needs of a more heterogeneous community, the community feels proud of the construction of the Mandalika Circuit, and some of the impacts on the economic sector and MSMEs. In addition to the positive impacts, negative impacts are also inevitable, let alone the erosion of one™s own culture which is full of good values. In the future, the community will not be complacent and will not be displaced by migrants because they are less competitive due to the limited competence of both hard skills and soft skills in the tourism sector. Researchers in the field of special socio-cultural studies due to the construction of the Mandalika Circuit are still not significant.